(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The theme of the Russian-Ukrainian war, described by Serhiy Loyko in the novel «Airport», is discovered in the article. Much attention is payed to the problem of patriotism and betrayal, average people’s suffering on both sides of the conflict. The major and minor characters’ images are analyzed.